Refining Unfavorable Vaginal Microbial Community in Infertile Women Subjected to Precision Probiotic Intervention: An Exploratory Single-Arm, Prospective, Open-Label, Interventional Study - Giovanna Cocomazzi; Viviana Contu; Silvia De Stefani; Lino Del Pup; Matteo Buccheri; Monica Antinori; Lodovico Parmegiani; Daniele De Ruvo; Francesco Marino; Edy Virgili; Christine Allen; Simone Palini; et al. (Microorganisms)
Background and aims: Vaginal microbiomes have been classified into five different general categories, termed Community State Type (CSTs), with CST-III and CST-IV often associated with vaginal dysbiosis which makes women more prone to recurrent infections and assisted reproductive technology (ART) failure. Since a healthy microbiome is one of the key steps for successful reproduction, we investigated the impact of modulating the vaginal microbiota through the oral administration of probiotic formula consisting of a consortium of vaginal-specific lactobacilli and prebiotics (Personal Flora 2®). Methods: We recruited 32 women who had previous failed IVF cycles and were scheduled to undergo ART. We examined the composition of the vaginal microbiota before and after oral probiotic supplementation using 16S ribosomal RNA (rRNA) sequencing technology. Results: Our data show a noticeable modulation of the vaginal microbiome upon probiotic supplementation. In particular, precision probiotic intervention lowers the species diversity, favoring the dominance of Lactobacillus (p = 0.015) and Bifidobacterium (p = 0.000) whilst decreasing the percentage of Atopobium (p = 0.003), Gardnerella (p = 0.022), and Prevotella (p = 0.000). Conclusions: Although CST-III and CST-IV are generally considered detrimental, gynecologists should not refrain from performing IVF in these women if they have been previously subjected to a consortium of precision probiotics treatments, as the administration of specific probiotics reduces the presence of pathogenic bacteria promoting the increase in lactobacilli associated with a healthy vaginal ecosystem, which could impact pregnancy success.